2011
DOI: 10.1111/j.1365-294x.2010.04997.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid formation of distinct hybrid lineages after secondary contact of two fish species (Cottus sp.)

Abstract: Homoploid hybridization after secondary contact between related species can lead to mixtures of genotypes which have the potential for rapid adaptation to new environmental conditions. Here, we focus on a case where anthropogenic changes within the past 200 years have allowed the hybridization between two fish species (Cottus rhenanus and Cottus perifretum) in the Netherlands. Specifically, we address the question of the dynamics of the emergence of these hybrids and invasion of the river systems. Using a set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 59 publications
1
89
0
Order By: Relevance
“…(2012) suggested that WEM was possibly a “hybrid swarm.” One of those features is the observation of increased fitness that should allow for ecological success to translate into evolutionary success (see, e.g., Pereira et al., 2014 for a marine example)—which could reflect adaptive introgression promoting the maintenance of hybrids (Hedrick, 2013; Martin, Bouck, & Arnold, 2006). Patterns of survival of the WEM × WEM cross go against high fitness of these “hybrids.” Adaptive introgression patterns or “swarming” at the center of the distribution of parental forms seems relatively common in other fish species (e.g., Machado‐Schiaffino, Juanes, & Garcia‐Vazquez, 2010; Roques, Sévigny, & Bernatchez, 2001; Sinama et al., 2013; Stemshorn, Reed, Nolte, & Tautz, 2011; Walters et al., 2008). However, while those studies described hybridization patterns using molecular markers, we are not aware of studies that reported fitness differences as carried out for WEM in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…(2012) suggested that WEM was possibly a “hybrid swarm.” One of those features is the observation of increased fitness that should allow for ecological success to translate into evolutionary success (see, e.g., Pereira et al., 2014 for a marine example)—which could reflect adaptive introgression promoting the maintenance of hybrids (Hedrick, 2013; Martin, Bouck, & Arnold, 2006). Patterns of survival of the WEM × WEM cross go against high fitness of these “hybrids.” Adaptive introgression patterns or “swarming” at the center of the distribution of parental forms seems relatively common in other fish species (e.g., Machado‐Schiaffino, Juanes, & Garcia‐Vazquez, 2010; Roques, Sévigny, & Bernatchez, 2001; Sinama et al., 2013; Stemshorn, Reed, Nolte, & Tautz, 2011; Walters et al., 2008). However, while those studies described hybridization patterns using molecular markers, we are not aware of studies that reported fitness differences as carried out for WEM in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We are studying the European freshwater sculpins Cottus rhenanus and Cottus perifretum because they can yield insights into the early evolutionary processes that lead to hybrid speciation (Nolte et al, 2005a;Nolte and Tautz, 2010;Stemshorn et al, 2011;Czypionka et al, 2012) and to learn about the genetic factors that mold narrow hybrid zones (Nolte et al, 2006(Nolte et al, , 2009. Briefly, man-made environmental changes within the past 200 years have increased the connectivity of the rivers Rhine and Scheldt and massively altered the ecological conditions in parts of these drainages.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis of these contact zones (Nolte et al, 2006(Nolte et al, , 2009 provides evidence that selection associated with different habitats counteracts genetic admixture. With respect to the evolution of the invasive lineage itself, a small fraction of the invasive genome appears to be subject to genotypic selection (Stemshorn et al, 2011). Further, an analysis of changes in gene expression provided evidence that novel phenotypes have evolved (Czypionka et al, 2012), which highlights the need to identify the evolutionary processes at work.…”
Section: Introductionmentioning
confidence: 99%
“…The relative importance of karyotypic differences versus genic incompatibilities is not known because there are relatively few studies specifically examining the genomic collinearity of homoploid hybrid species and their progenitors (but see Rieseberg et al, 1995;Lai et al, 2005). While studies in Helianthus support chromosomal differences as a largely important barrier to gene flow (Rieseberg et al, 1995;Lai et al, 2005), a recent study in Cottus (Stemshorn et al, 2011) and the current study reveal high degrees of genomic collinearity between the homoploid hybrid lineage and the progenitors, suggesting that other mechanisms are potentially responsible for reproductive isolation between the hybrid lineage and progenitors. The genomes of all four hybridizing Louisiana Iris species show a high degree of genetic collinearity.…”
Section: Genomic Collinearitymentioning
confidence: 99%